Broadening Versus Deepening: Gender and Brokering in Social Networks. Issue 2 (March 2022) - Halevy, Nir; Kalish, Yuval
Do women and men differ in their brokering behavior? Integrating the literatures on gender, self-construal, and social networks, we theorize that gender differences in relational interdependence produce different patterns of helpful brokering among women versus men. Two experiments tested the hypothesis that tie strength moderates the effect of gender on two types of helpful brokering: helping others form new network ties (intermediary brokering) and helping others repair strained network ties (conciliatory brokering). In both experiments, the observed gender by tie strength interactions were driven by gender differences in network-broadening behavior (i.e., willingness to help weak ties) rather than network-deepening behavior (i.e., willingness to help strong ties). Experiment 2 provides evidence that differences in relational self-construal mediate the effect of gender on brokering behavior. We discuss the implications of these findings for gender inequality in organizations and in society.